A security patch for your brain. (Economist, 2012)
The author reflects on research related to computer passwords. The author points out that users often select insecure passwords that are easy to remember. Researchers suggest choosing passphrases of multiple unrelated words, which are harder for criminals to decode. Also suggested is using the first letters of words in a mnemonic sentence.